Super Trawler Scuppered in Australian Fisheries Management Reform. Issue 8 (14th August 2013) - Tracey, Sean; Buxton, Colin; Gardner, Caleb; Green, Bridget; Hartmann, Klaas; Haward, Marcus; Jabour, Julia; Lyle, Jeremy; McDonald, Jan
ABSTRACT: In response to an intense social media campaign led by international conservation groups, Green politicians, and recreational fishers, the Australian government imposed a moratorium on the operations of a large factory trawler. This moratorium overrode the government's own independent fisheries management process by making amendments to its key environmental legislation just days prior to the commencement of fishing by this vessel. Concurrently, the government announced a comprehensive review of Australia's fisheries management legislation. Whereas science is usually deployed in support of conservation in natural resource conflicts, in this case science‐based fisheries management advice took a back seat to vociferous protest by interest groups, perpetuated by the media (in particular social media), ultimately culminating in a contentious political decision.